Nghiên cứu hành vi khách hàng đối với thanh toán di động QR-code: Thực nghiệm trong bối cảnh COVID-19 - Lê Xuân , Cù; Nguyễn Thị Hải , Yến; Vũ Thị Hồng , Thu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The paper aims to identify vital factors influencing behavioral intentions of customers toward mobile QR-code payment in a COVID-19 context. This study formulates a theoretical model by combining Unified Theory of Acceptance and Use of Technology (UTAUT) and Health Belief Theory (HBT). Empirical data were collected from a sample of 405 respondents who have experienced making online transactions via QR-code payment or have tendencies to utilize QR-code payment in Hanoi. Statistical analysis was conducted using AMOS 22.0 to test the hypotheses. The results indicate that usage intention is motivated by the antecedents from UTAUT (i.e., performance expectancy, effort expectancy, social influence, and facilitating conditions) and crucial factors from HBT (i.e., perceived severity, and self-efficacy). Moreover, social distancing is an indispensable motivator of usage intention toward QR-code payment under COVID-19. Furthermore, a strong relationship between usage intention and recommendation intention demonstrates the effectiveness of QR-code payment. Theoretical and practical implications are discussed in this work.